Effect of surfactant type on synthesis and characteristics of nanonickel hydroxide - Stephen Lim; Ratna Frida Susanti; Gelar Panji Gemilar; Widi Astuti; Himawan Tri Bayu Murti Petrus; Kevin Cleary Wanta (Jurnal Rekayasa Proses, 2021)
Nickel hydroxide has a vital role in various applications, especially as a support material for energy storage materials. Nickel hydroxide can be synthesized through the hydroxide precipitation method. However, the product formed by this method may be large or more than 100 nm because the agglomeration step can occur easily. This present work aims to study the effect of surfactant types in the synthesis and characterization of nickel hydroxide nanoparticle. Nickel sulfate (NiSO4) solution was used as a precursor solution, while 5M sodium hydroxide (NaOH) solution was used as a precipitation agent. The surfactants studied were alkyl benzene sulfonate (ABS), sodium dodecyl sulfate (SDS), cetyltrimethylammonium bromide (CTAB), and polyvinylpyrrolidone (PVP). The nickel hydroxide synthesis process was carried out at 50 oC for 1 hour. The surfactant concentration used was at the critical micelle concentration (CMC), where the CMC for ABS, SDS, CTAB, and PVP were 0.01; 0.05; 3; and 0.5 %w/v, respectively. The synthesis of nickel hydroxide nanoparticle was carried out successfully precipitated almost 100% of Ni2+ ions. The product characterization that has been carried out shows that ABS surfactant produces the best nickel hydroxide nanoparticle product where the particle size is 3.12–4.47 nm.